Investigation of shielding material properties for effective space radiation protection. (August 2020) - Naito, Masayuki; Kodaira, Satoshi; Ogawara, Ryo; Tobita, Kenji; Someya, Yoji; Kusumoto, Tamon; Kusano, Hiroki; Kitamura, Hisashi; Koike, Masamune; Uchihori, Yukio; Yamanaka, Masahiro; Mikoshiba, Ryo; et al.
Abstract: Geant4 Monte Carlo simulations were carried out to investigate the possible shielding materials of aluminum, polyethylene, hydrides, complex hydrides and composite materials for radiation protection in spacecraft by considering two physical parameters, stopping power and fragmentation cross section. The dose reduction with shielding materials was investigated for Fe ions with energies of 500 MeV/n, 1 GeV/n and 2 GeV/n which are around the peak of the GCR energy spectrum. Fe ions easily stop in materials such as polyethylene and hydrides as opposed to materials such as aluminum and complex hydrides including high Z metals with contain little or no hydrogen. Attenuation of the primary particles in the shielding and fragmentation into more lightly charged and therefore more penetrating secondary particles are competing factors: attenuation acts to reduce the dose behind shielding while fragmentation increases it. Among hydrogenous materials, 6 Li 10 BH4 was one of the more effective shielding materials as a function of mass providing a 20% greater dose reduction compared to polyethylene. Composite materials such as carbon fiber reinforced plastic and SiC composite plastic offer 1.9 times the dose reduction compared to aluminum as well as high mechanical strength. Composite materials have been found to be promising for spacecraft shielding, where both mass and volume are constrained.